Analisis Deiksis dalam Cerpen "Jakarta" Karya T. Tjitrawasita (Suatu Pendekatan Stilistika)) - ST. Nursaadah (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This article entitle "Analysis of Dieksis in Short Story of Jakarta by T. Tjitrawasita (A Review Stilistika)". This article used stilistika approach. This is important because language literature using language media in a typical expression. Stilistika approach, meaning through force disclosure works in a literary works can be expressed objectively. The purposes of this article is to reveal the role deiksis in a work of literature (short stories) that can express the meaning of a work through the built elements such as character, setting, plot, and theme. The method of writing is descriptive qualitative. The source data comes from the primary data through the work itself is a short story Jakarta and secondary data through multiple sources of reference that has nothing to do with the primary data. The result showed that deiksis used not only as a style, not having any role, but the choice deiksis able to give meaning to a work typically.